Features of Using the Regional Component in Training Students of Program Subject Area 242 «Tourism» - Dolynska, Olesia (Pedagogical Discourse, 2021)
The article considers the possibilities of using the regional component in the training of students of Program Subject Area 242 «Tourism». The uniqueness of the educational program lies in the development of tourism in the formation and development of territorial communities of Khmelnytsky region. Cooperation with regional enterprises has been established. Applicants are involved in the practical development and implementation of a tourist product within the project «Tourist Magnets». There is a scientific circle «Tourism Expert».The regional component is presented in disciplines. It is noted that the development of the regional tourist complex of Khmelnytsky region is influenced by the interaction of the following factors: economic, social, natural, environmental. Social infrastructure is important for the organization of full-fledged recreation of tourists: the availability of housing and communal services, cultural and household services, health care, trade. The current available nature reserve and historical and cultural funds of Khmelnytsky region are used very unevenly. The regional tourist complex of Khmelnytsky region consists of 58 point elements of the territorial structure and two dispersed tourist bushes with nodes in the cities of Kamyanets-Podilsky and Khmelnytsky. There are 18 mono- and 17 bifunctional tourist points and 1 mono- and 10 bifunctional centers, as well as 1 mono- and 2 bifunctional clusters in the region.The main branch directions of perspective development of tourist activity of Khmelnytsky region which need to be realized through carrying out of changes in the territorial organization of a regional tourist complex are specified. Emphasis is placed on the main problems in the development of the tourist complex of Khmelnytsky region. This knowledge is important in the preparation of students of Program Subject Area 242 «Tourism».